1908 Md. Laws 397 - (:unkn) unknown (My University, 1908)
§ 31: It shall be unlawful for any person under the age of twenty-one years to fire a gun, cat rifle, pistol, or any explosive instrument of metal, within one mile in any direction of the Library Hall in Catonsville, Baltimore county; and any person under said age of twenty-one years, violating this section, shall upon conviction before the Circuit Court, or any justice of the peace for said county, be fined a sum not less than one dollar nor more than ten dollars, or be imprisoned in the county jail for not less than five days nor more than thirty days, or be both fined and imprisoned, in the discretion of the court or the justice of the peace.
Keywords: DISCHARGE